EFFECTIVENESS OF âFASTâ STROKE CAMPAIGN FOR FAST STROKE RECOGNITION AND RESPONSE: A SYSTEMATIC REVIEW - Sudirman, Herpani; Yuliyanti, Citra; Sari, Andrea Indra (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: FAST campaigns help people recognize the signs and symptoms of stroke rapidly to bring the patient to the hospital or emergency department immediately. However, the effectiveness is still be questioned. This present study is to evaluate the effectiveness of the campaign of early detection in stroke patients to reduce the risk of disability. Methods: A systematic review of articles published between 2010 and 2017 examining the effectiveness of FAST campaign using interventions was conducted along with narrative synthesis and review of intervention development. Information from all relevant published articles that determine how the intervention was developed and evaluated for measuring the effectiveness of FAST campaign were extracted and analyzed. Results: Eleven studies were included, six studies report the effectiveness of FAST campaign, but the other five studies report that the campaigns still do not hit the target. The professionals claim that FAST campaign has been promoted internationally as a great success, but some studies report that the FAST campaign still do not have any significant impact in promoting swift response for Emergency Medical Services (EMS). Conclusions: Campaigns aimed at the public may raise awareness of signs of stroke, but have limited impact on behavior. Thus, new campaigns of FAST should survey the principles of good design and be intensely evaluated for the effectiveness of the implementation.Â